2011
DOI: 10.1111/j.1440-1789.2011.01222.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive distribution of glial cytoplasmic inclusions in an autopsied case of multiple system atrophy with a prolonged 18‐year clinical course

Abstract: We describe herein an autopsied case of multiple system atrophy (MSA) with prolonged clinical course of 18 years, and evaluate the extent of neurodegeneration and glial cytoplasmic inclusions (GCIs) in the entire brain of this rare case. A 64-year-old woman presented with typical neurological symptoms and imaging features of MSA. Thereafter, she became bedridden, and breathing was assisted through a tracheostomy for 12 years. She died at the age of 82 after 18 years from the initial symptom. Post mortem examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…This case manifesting only mild clinical symptoms was recently suggested to represent “early MSA” rather than “minimal change” MSA . Rare cases of MSA‐P with slow progression and prolonged survival were considered an uncommon “benign” subgroup, whereas another case with prolonged clinical course of 18 years showed extensive distribution of GCIs in wide CNS areas . A subgroup with severe temporal atrophy showed numerous NCIs, particularly in the limbic system .…”
Section: Rare Subtypes Of Msamentioning
confidence: 95%
“…This case manifesting only mild clinical symptoms was recently suggested to represent “early MSA” rather than “minimal change” MSA . Rare cases of MSA‐P with slow progression and prolonged survival were considered an uncommon “benign” subgroup, whereas another case with prolonged clinical course of 18 years showed extensive distribution of GCIs in wide CNS areas . A subgroup with severe temporal atrophy showed numerous NCIs, particularly in the limbic system .…”
Section: Rare Subtypes Of Msamentioning
confidence: 95%
“…Many of these patients developed motor fluctuations and levodopa-induced choreiform dyskinesias, which would have indicated deep brain stimulation, not recommended for MSA patients [ 320, 321 ]. These rare long surviving patients with MSA-P were considered “benign” forms [ 43 ], whereas other cases with clinical course of 18 years revealed extensive distribution of GCIs in CNS [ 322 ]. A non-motor variant of pathologically confirmed MSA showed neither parkinsonism nor cerebellar symptoms [ 323 ].…”
Section: Neuropathologymentioning
confidence: 99%
“…Despite the primarily oligodendrocytic accumulation of α‐syn, MSA patients also display considerable neuronal loss in the striatum, cerebellum, brainstem and cortex, accompanied by astrogliosis, microgliosis and myelin loss (173, 182). Interestingly, a recent study has reported p62 immunoreactivity (a ubiquitin‐associated autophagy substrate) in GCIs of a MSA patient (109) highlighting the possibility that autophagocytic alterations may also play a role in this disorder.…”
Section: Alterations In Autophagy In α‐Synucleinopathiesmentioning
confidence: 99%